The Impact of the Implementation of the Regulation of the Minister of Maritime Affairs and Fisheries of the Republic of Indonesia on the Traffic Volume of Lobster (Panulirus Spp.) in Gorontalo Province - Dewi Shinta Achmad; Muh. Saleh Nurdin; Indri Afriyani Yasin; Merita Ayu Indrianti; Meity M Mokoginta; Mohammad Ervandi; Dewa Oka Suparwata; Yusriyah Atikah Gobel; Talha Dangkua (Newinera Publisher, 2022)
Impacts of Implementation Regulation of The Ministry of Marine Affairs and Fisheries No. 1/Permen-Kp/2015 to Lobster Traffic Volume in Gorontalo Province. The implementation of the Permen NO. 1/PERMEN-KP/2015 with the aim to protect, preserve, and utilize crustacean resources. This study aimed to analize impact of implementation Permen NO. 1/PERMEN-KP/2015 to lobster traffic volume in Gorontalo Province. The research result that highest of lobster traffic volume on 2012 and lowest on 2016. There was a significant difference (p <0.05) between lobster traffic volume before and after implementation of Permen KP NO. 1/PERMEN-KP/2015. Implementation of Permen KP NO. 1/PERMEN-KP/2015 turned positive impact to lobster because provides a lobster opportunity to regenerate.